Physiological changes during pregnancy and its importance in anesthesiology - Enciso Nano, Jorge (2015)
The anesthetic management of a pregnant patient, involves a lot of responsibility on the part of the anesthesiologist, since the lack of normal physiological changes that occur in pregnant women may cause lethal accidents fetal mother with great impact. The use of the technique of conductive anesthesia for caesarean section, will occur in the patient's hemodynamic changes by vasoplegia own art; and if previously before producing the blockage is not the physiological changes that occur during pregnancy are corrected, it will produce decreased venous return is going to affect cardiac output consequently resulting in severe hypotension mother with altered acid-base balance maternal and fetal, likewise, the use of the technique General anesthesia a patient to be subjected to emergency Caesarean section, if the anesthetic induction and intubation is not fast will occur in aspiration patient vomiting, the tracheobronchial tree producing Aspiration pneumonitis the lethal consequence of the mother. The aim of this review is to remind colleagues anesthesiologists normal physiological changes that occur in pregnant women to avoid accidents during surgery that will impact on how severe the mother-child pair, thus desprestigiándose group specialists who make the surgical team.